Silica nanoparticles surface charge modulation of the electroactive phase content and physical-chemical properties of poly(vinylidene fluoride) nanocomposites - Ribeiro, Sylvie (2020)
Composites based on a piezoelectric polymer (PVDF) doped with different silica nanoparticles (SiNPs) content (8, 16 and 32wt%) and functionalization (WF-without, NF-negative and PF-positive) have been investigated. Composite films were prepared by solvent casting and melt crystallization to investigate the effect of the presence of the SiNPs on the physico-chemical characteristics and, in particular, in the nucleation of the electroactive -phase of the polymer. It is shown that the introduction of the SiNPs allows to increase water surface angle up to 34% with respect to -PVDF, as well to increase the elastic modulus. Filler content and type have an important effect on the nucleation of the electroactive beta phase content and the dielectric properties of the composites, the larger values of both being obtained for positively surface charged nanoparticles. It is concluded that, taken into consideration the overall properties of the composites, the SiNPs-PF/PVDF nanocomposites with 8wt% filler content offer a promising approach for applications due to the improvement of the electroactive phase of PVDF.